Representasi Kecantikan dalam Iklan Pond’s Bright Miracle Facial Foam ft. Tzuyu Twice: Kajian Semiotika dengan Teori Charles Sanders Peirce - s, dini_22 (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2025)
Abstract This research aims to analyze and understand articles from Pond's Bright Miracle Facial Foam advertisements through a semiotic approach using the theory of Charles Sanders Peirce. This analysis was carried out to identify icons, indices and symbols contained in Pond's Bright Miracle Facial Foam advertisements. Advertising often displays ideal beauty standards to influence people's views on a product. This research analyzes the symbols contained in the Pond's Bright Miracle Facial Foam advertisement through beauty narratives that are synonymous with smooth and glowing skin texture. Through analysis using Pierce's theory, it represents that beauty, symbolized by smooth and glowing skin, can be obtained from using products. These beauty standards become part of a person's self-confidence and happiness. The beauty displayed by the model not only functions as a symbol, but can also build people's perspective about the product being marketed. Keywords: representation of beauty, advertising, Fair & Lovely, semiotics, Charles Sanders Peirce